Novel Ribosome-inactivating Protein (RIP) Isolated from Trichosanthes dioica Induces Apoptosis in HeLa Cell Line - Ghosh, T.; Vashi, Y.; Barman, K.; Singha, L. I. (International Journal of Bio-resource and Stress Management, 2021)
Ribosome-inactivating proteins (RIPs) are toxic N-glycosidases that depurinate eukaryotic and prokaryotic rRNAs and thus interrupt protein synthesis during translation. In the present study, a protein of around 32 kDa, supposedly a RIP isolated from Trichosanthes dioica, was assessed for its potential to induce apoptosis in HeLa cells. Cell viability assay was done to measure cell proliferation and survivability. It was observed that cells viability decreased with the increase of decrease in dilution, i.e. when the sample was an undiluted one, the viability decreased drastically and almost came to less than 10%. To further check whether the isolated RIP could induce apoptosis, HeLa cells were treated with the test RIP. Immunoblotting was carried out using PARP poly (ADP-ribose) polymerase (PARP-1), a 113 kDa nuclear enzyme, which is considered a hallmark of cells undergoing apoptosis. HeLa cells were further analyzed for loss of mitochondrial membrane potential with JC-1 dye, which is an early event during apoptosis. Increased PARP breakdown in the RIP treated cells indicates that cells undergoing apoptosis and progressive loss of red J-aggregate fluorescence indicate that the isolated RIP from Trichosanthes dioica induces apoptosis in HeLa cells. The ability of apoptosis induction is comparable to another known RIP from Momordica charantia, which was used as a positive control. Promising results from the present study warrants the isolated RIP to be further explored for anticancer activities.